Analisis Penggunaan Bahasa Pada Lirik Lagu “Kita Pasti Tua” Karya Fourtwnty Sebagai Pesan Moral - Muhammad Raihan Chandra Gunawan; Muhammad Noor Dzacky (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
The quote "We Must Be Old" from Fourtwnty is not just a song, but a journey within oneself. Through rich and meaningful lyrics, we are invited to reflect on life and the process of growing old. Like poetry that is pleasant to listen to, but also makes us think deeply. His choice of words is topnotch. "White hair", "creased forehead", and "low energy" describe the aging process that we all experience. These straightforward and touching words make us look back, look at the journey of our lives, and think about how precious the passing of time is. Apart from word choice, these lyrics are also good at playing with language styles. There are similes like "steps that used to be nimble, now are limping" and personifications like "time keeps turning around." This style of language not only makes the lyrics cute, but also reminds us that aging is a natural thing and we must accept it gracefully. The lyrics are neatly arranged and the sentences vary in length. There are short sentences that are catchy, there are also long sentences that are full of meaning. This combination makes the song enjoyable to follow and the moral message is even more touching to the heart. "We Must Be Old" is more than just a song. This is Fourtwnty's invitation to make us reflect on the meaning of life, accept aging, and understand how precious time is. Every second is precious and will never come back again.